Way ahead - Post Covid-19 Lockdown in India - Rana, Manish; Kundapur, Rashmi; Maroof, Amir; Chaudhari, Vipul; Kadri, Amiruddin; Kumar, Pradeep; Zodpey, Sanjay; Garg, Suneela; Agrawal, Arun; Bapat, Nirav (Indian Journal of Community Health, 2020)
COVID 19 pandemic is a global health emergency which every country is grappling with since beginning of this year. Countries have their own strategies to cope with the cases and there have been no universal guidelines or recommendations for same. We commend the Hon. Prime Minister for taking pre-emptive timely measures to contain the pandemic at very beginning of infection in India as sustaining containment measures. Even the World Health Organisation (WHO) has acknowledged India’s efforts. According to experts for effective herd immunity about 60% of population needs to be infected, after which the infection will slow down and cases will continue to occur at low levels. For that we need good data coming from the system and government shall ensure that good data is provided for monitoring and surveillance. If all the susceptible population is exposed (without any restrictions) then we have an exponential rise in cases and our health system will be overwhelmed probably resulting in large number of deaths. Great Britain went ahead with strategy of developing herd immunity in its population and safeguarding the elderly but after projections from Imperial College COVID 19 team, reversed their strategy to social distancing and saving lives as their health system will be overwhelmed. COVID 19 is a mild disease for people in the younger age group while in people above the age of 60 years, the mortality is high. So staggered exposure of younger population to infection while safeguarding the elderly population at home will prevent the surge of cases and facilitate gradual development of immunity in population. Government should also focus on developing a robust health care system for screening and management of cases coupled with gradual relaxation of restriction so that health system is not overwhelmed with management of COVID 19.